2003
DOI: 10.1093/annonc/mdg299
|View full text |Cite
|
Sign up to set email alerts
|

P21WAF1, P27KIP1, TP53 and C-MYC analysis in 204 ovarian carcinomas treated with platinum-based regimens

Abstract: We have shown an independent predictive value of P21(WAF1) LI in ovarian carcinoma patients. The prognostic value of P21(WAF1) and P21(WAF1) plus P27(KIP1) LI was determined by TP53 status. A high frequency of C-MYC overexpression in endometrioid and clear cell carcinomas may suggest its role in the development of these tumor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
5
28
2
1
Order By: Relevance
“…Inactivation of p53 function leads to loss of p21 Waf1/Cip1 induction and impairment of cyclin/CDK complex inhibition. Indeed, we found that 77% of serous EOC in our cohort had low or no expression of p21 Waf1/Cip1 , which was significantly associated with poor survival and a shorter progression-free interval, as previously demonstrated by others (41)(42)(43)(44). In addition, we found significant loss of p21 Waf1/Cip1 expression in tumors that overexpressed p53, although this did not seem to be the case in all tumors.…”
Section: Loss Of P16supporting
confidence: 86%
“…Inactivation of p53 function leads to loss of p21 Waf1/Cip1 induction and impairment of cyclin/CDK complex inhibition. Indeed, we found that 77% of serous EOC in our cohort had low or no expression of p21 Waf1/Cip1 , which was significantly associated with poor survival and a shorter progression-free interval, as previously demonstrated by others (41)(42)(43)(44). In addition, we found significant loss of p21 Waf1/Cip1 expression in tumors that overexpressed p53, although this did not seem to be the case in all tumors.…”
Section: Loss Of P16supporting
confidence: 86%
“…Baekelandt et al (1999) found no correlation between expression of p21 and p27 in ovarian cancer and response to chemotherapy with epirubicin and cisplatin. Another study showed in vivo a better response to platinum based chemotherapy with high p21 expression in ovarian cancer (Plisiecka-Halasa et al 2003). Our study could not prove any association between expression of cki p21 and p27 and chemotherapy response, but only a small subgroup of our patients could be evaluated and the number of patients for statistical analysis is very small.…”
Section: Multivariate Analysis For Prognostic Factorsmentioning
confidence: 63%
“…Similarly, decreased p27 expression (as reported in 55% of OC), showed an independent association with poor survival in patients with advanced OC [10]. The simultaneous assessment of multiple cyclerelated proteins could be particularly useful in the prognostic stratification of OC [4,9].…”
Section: Loss Of Cell Proliferation Controlmentioning
confidence: 94%
“…Concerning with the CDK inhibitors, the expression of p21 is lost in 25-75% of OC [4,7,8] and low p21 expression is associated with: high tumor grade [4], advanced stage and residual tumor after surgery [7], and low response rate to platinum-based chemotherapy [9]. Similarly, decreased p27 expression (as reported in 55% of OC), showed an independent association with poor survival in patients with advanced OC [10].…”
Section: Loss Of Cell Proliferation Controlmentioning
confidence: 99%